PERANCANGAN SISTEM INFORMASI PELACAKAN LAYANAN PERBAIKAN BERBASIS CUSTOMER RELATIONSHIP MANAGEMENT UNTUK PERUSAHAAN JASA SERVICE CENTER (STUDI PADA T-COMP JOGJA) - , AGUS SETIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Key to the company's success not only from the quality of products/services, but how far the company's efforts to satisfy customers' needs and then provide good service and fun they are to ensure that they become loyal customers. CRM allows the creation of customer loyalty not only in its products but also loyal to the company. The implementation of CRM strategies can be developed to acquire new customers, improve customer relationships, and retaining customers that led to the creation of customer loyalty. This study aims to design a repair serviceS tracking information system based on CRM that is focused on a services center T-Comp Jogja. There are six stages in this research to be traversed, the first are interviews and observations, the second is a collection of requirements, the third is the design of information systems, the fourth is the development of information systems, the fifth is the testing of the results of design and development, and the sixth is the conclusion and suggestions. The method for the development of the information system using rapid application development (RAD). The study produced several conclusions, among which is a prototype repair services tracking information system based on CRM for the services center consists of six main tables, user, items, notes, complaints, handling, and history of handling. The main process of this prototype, there are two, customer management and service management.